2020
DOI: 10.3892/etm.2020.9288
|View full text |Cite
|
Sign up to set email alerts
|

miR‑132 improves the cognitive function of rats with Alzheimer's disease by inhibiting the MAPK1 signal pathway

Abstract: Alzheimer's disease (AD) is a common worldwide progressive neurodegenerative disease. The dysregulation of miRNA is crucial in neurodegenerative diseases and neuron apoptosis during AD and is closely associated with the MAPK pathway. By bioinformatic website, we found that there was target inhibiting relationship between microRNA (miR)-132 and MAPK1. Therefore, the current study speculated that miR-132 could improve the cognitive function of rats with AD by inhibiting MAPK1 expression. To verify our hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 43 publications
(52 reference statements)
1
45
0
Order By: Relevance
“…Neuron apoptosis during AD is closely associated with the MAPK pathway ( Li et al, 2019 ). In the study by Deng et al (2020) miR-132 expression was significantly downregulated in an AD rat model, and MAPK1 expression was significantly upregulated; they suggested that miR-132 and MAPK1 had specific binding sites, and that miR-132 could inhibit MAPK1 expression. They concluded that miR-132 can inhibit hippocampal oxidative stress and iNOS expression by inhibiting MAPK1 expression to improve the cognitive function of AD rats ( Deng et al, 2020 ).…”
Section: Neuropathogenesis and Neuroprotection Of Mir-132 In Ad: Implications From In Vivo And In Vitro mentioning
confidence: 99%
“…Neuron apoptosis during AD is closely associated with the MAPK pathway ( Li et al, 2019 ). In the study by Deng et al (2020) miR-132 expression was significantly downregulated in an AD rat model, and MAPK1 expression was significantly upregulated; they suggested that miR-132 and MAPK1 had specific binding sites, and that miR-132 could inhibit MAPK1 expression. They concluded that miR-132 can inhibit hippocampal oxidative stress and iNOS expression by inhibiting MAPK1 expression to improve the cognitive function of AD rats ( Deng et al, 2020 ).…”
Section: Neuropathogenesis and Neuroprotection Of Mir-132 In Ad: Implications From In Vivo And In Vitro mentioning
confidence: 99%
“…Tau phosphorylation can be modulated by some miRNAs, namely, miR-200a-3p, miR-326, miR-124-3p, miR-146a, miR-425-5p, and miR-132. Expression of miR-132 has been assessed by several investigations with most of them reporting its downregulation in AD (Wong et al, 2013 ; El Fatimy et al, 2018 ; Cha et al, 2019 ; Deng et al, 2020 ). Yet, Liu et al have reported over-expression of miR-132 in patients with mild cognitive impairment and AD vs. normal individuals (Liu and Zhang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in a rat model of AD have shown upregulation of AChE, iNOS, ROS, MDA, MAPK1, and p-MAPK1 and downregulation of SOD, GSH-Px, and miR-132. Over-expression of miR-132 has reversed these markers demonstrating the role of this miRNA in the suppression of hippocampal iNOS expression and oxidative stress through reduction of MAPK1 levels (Deng et al, 2020 ). However, expression of this miRNA has been demonstrated to be reduced in neurally-originated plasma exosomes of AD subjects (Cha et al, 2019 ).…”
Section: Dysregulated Mirnas In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Number of article Route of Administration ICV IP Oral Sub-cutaneous Amyloid β** 35 [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34]. [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47] 35 0 0 0 Streptozotocin** 16 [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63] 16...…”
Section: Toxic Substancesmentioning
confidence: 99%